Rapid Microwave‐Assisted Synthesis of CdS/Graphene/MoSx Tunable Heterojunctions and Their Application in Photocatalysis. Issue 29 (13th March 2020) - Tzanidis, Iordanis; Bairamis, Feidias; Sygellou, Lamprini; Andrikopoulos, Konstantinos S.; Avgeropoulos, Apostolos; Konstantinou, Ioannis; Tasis, Dimitrios
Abstract: Nanoscale two‐dimensional nanostructures have shown great potential as functional components in photocatalysis. Here, investigations on the synthesis of heterostructured hybrids, comprised of 0D CdS nanoparticles as semiconductor and 2D/2D graphene/MoS x as co‐catalyst, are reported. The approach involves a rapid microwave‐assisted reaction in autoclave conditions, by adopting either a one‐step or a two‐step protocol. The chemical speciation of the nanocomposites was found to depend strongly on the compounding conditions of the precursor substances. The photocatalytic activity was assessed by monitoring the photodegradation rate of 4‐nitrophenol in solution using simulated solar light irradiation. The photocatalytic activity of the hybrids may be attributed to a combination of beneficial characteristics, strongly related to the chemical speciation of the composite components. Moreover, intimate contacts of the latter result in efficient heterojunctions. Overall, the present study provides valuable insight into the development of functional heterostructured photocatalysts comprised of two‐dimensional nanomaterials. Abstract : 2D/2D graphene/MoSx heterojunctions are employed as co‐catalyst in CdS‐based hybrids for photocatalytic activity enhancement. The rapid microwave‐assisted synthetic protocol requires moderate temperatures. The enhanced photodegradation of nitroarene is attributed to a few advantageous synergetic parameters, such as intimate contacts between the components of the hybrid and the chemical speciation of the nanostructured materials.